The Plasmodium falciparum exported J domain proteins fine-tune human and malarial Hsp70s: pathological exploitation of proteostasis machinery - Almaazmi, Shaikha Y.; Kaur, Rupinder P.; Singh, Harpreet; Blatch, Gregory L. (Frontiers in Molecular Biosciences, 2023)
Cellular proteostasis requires a network of molecular chaperones and co-chaperones, which facilitate the correct folding and assembly of other proteins, or the degradation of proteins misfolded beyond repair. The function of the major chaperones, heat shock protein 70 (Hsp70) and heat shock protein 90 (Hsp90), is regulated by a cohort of co-chaperone proteins. The J domain protein (JDP) family is one of the most diverse co-chaperone families, playing an important role in functionalizing the Hsp70 chaperone system to form a powerful protein quality control network. The intracellular malaria parasite, Plasmodium falciparum, has evolved the capacity to invade and reboot mature human erythrocytes, turning them into a vehicles of pathology. This process appears to involve the harnessing of both the human and parasite chaperone machineries. It is well known that malaria parasite-infected erythrocytes are highly enriched in functional human Hsp70 (HsHsp70) and Hsp90 (HsHsp90), while recent proteomics studies have provided evidence that human JDPs (HsJDPs) may also be enriched, but at lower levels. Interestingly, P. falciparum JDPs (PfJDPs) are the most prominent and diverse family of proteins exported into the infected erythrocyte cytosol. We hypothesize that the exported PfJPDs may be an evolutionary consequence of the need to boost chaperone power for specific protein folding pathways that enable both survival and pathogenesis of the malaria parasite. The evidence suggests that there is an intricate network of PfJDP interactions with the exported malarial Hsp70 (PfHsp70-x) and HsHsp70, which appear to be important for the trafficking of key malarial virulence factors, and the proteostasis of protein complexes of human and parasite proteins associated with pathology. This review will critically evaluate the current understanding of the role of exported PfJDPs in pathological exploitation of the proteostasis machinery by fine-tuning the chaperone properties of both human and malarial Hsp70s.